The Heterosexual Script on Tween, Teen, and Young-Adult Television Programs: A Content Analytic Update and Extension. Issue 9 (21st November 2020) - Aubrey, Jennifer Stevens; Yan, Kun; Terán, Larissa; Roberts, Lindsay
ABSTRACT: In a well-cited 2007 paper in Journal of Sex Research, Kim and colleagues proposed and documented a heterosexual script on primetime television. In the present study, we provide a 15-year update on the portrayal of the heterosexual script, and we further examine how it relates to three contextual variables: target age of the audience, age of the characters, and relational context of the script. Drawing from a 2016 sample of television programs that featured tween, teen, or young-adult characters, we documented three complementary sexual scripts: the sexual double standard (sexuality is equated with masculinity, women's virtue is tied to their sexuality), commitment (men avoid commitment, women seek it), and homophobia (men must avoid homosexuality, female homosexuality is voyeuristically appealing to men). Like the Kim et al. study, the dominant heterosexual script was sex as masculinity; this script was equally represented in tween, teen, and young-adult shows. The second most common script was that men prioritize sex over commitment, followed by the notion that women's virtue is tied to their sexuality. The commitment scripts were most often invoked by young-adult and adult characters, while the sexual double standard scripts were more pronounced in hookups than in committed relationships.